Human parasitic infections of the class Adenophorea: global epidemiology, pathogenesis, prevention and control - Jitrawadee Intirach; Chang Shu; Xin Lv; Suzhen Gao; Nataya Sutthanont; Tao Chen; Zhiyue Lv (BMC, 2024)
Abstract Background Human parasitic infections caused by Adenophorean nematodes encompass a range of diseases, including dioctophymiasis, trichuriasis, capillariasis, trichinellosis, and myositis. These infection can result in adverse impacts on human health and cause societal and economic concerns in tropical and subtropical regions. Methods This review conducted searches in PubMed, Embase and Google Scholar for relevant studies that published in established databases up to April 26, 2024. Studies that focused on the common morphology, life cycle, disease distribution, clinical manifestations, and prevention and control strategies for Adenophorean parasitic diseases in humans were included. Results Adenophorean nematodes exhibit shared morphological characteristics with a four-layered cuticle; uninucleate epidermal cells; pseudocoelom with six or more coelomocytes; generally three caudal glands; five esophageal glands; two testes in males with median-ventral supplementary glands in a single row; tail in males rarely possessing caudal alae; amphids always postlabial; presence of cephalic sensory organs; absence of phasmids; and a secretory-excretory system consisting of a single ventral gland cell, usually with a non-cuticularized terminal duct. Humans play two important roles in the life cycle of the nematode class, Adenophorea: 1) as a definitive host infected by ingesting undercooked paratenic hosts, embryonated eggs, infective larvae in fish tissue and meat contaminated with encysted or non-encysted larvae, and 2) as an accidental host infected by ingesting parasitic eggs in undercooked meat. Many organs are targeted by the Adenophorean nematode in humans such as the intestines, lungs, liver, kidneys, lymphatic circulation and blood vessels, resulting in gastrointestinal problems, excessive immunological responses, cell disruption, and even death. Most of these infections have significant incidence rates in the developing countries of Africa, Asia and Latin America; however, some parasitic diseases have restricted dissemination in outbreaks. To prevent these diseases, interventions together with education, sanitation, hygiene and animal control measures have been introduced in order to reduce and control parasite populations. Conclusions The common morphology, life cycle, global epidemiology and pathology of human Adenophorean nematode-borne parasitic diseases were highlighted, as well as their prevention and control. The findings of this review will contribute to improvement of monitoring and predicting human-parasitic infections, understanding the relationship between animals, humans and parasites, and preventing and controlling parasitic diseases. Graphical Abstract